A Simplified 3D Model for Tunnel Pile Interaction - Nawel Bousbia (Selected Scientific Papers: Journal of Civil Engineering)
Due to the development of communication routes (metro, railways), it is frequently necessary to build underground structures in order to improve traffic flow, which is a key factor in the metropolitan areas’ regeneration. Taking in account of the interaction between tunnel-soil-piles is a significant topic and a vital factor in the analysis the total solutions of these underground projects. The significance of the impacts communicated depends on a number of factors, including the genre of structure, and the soil type. The main purpose of the present paper is to study numerically the immediate influences that will result from the new tunnels construction near existed piles (micropiles), this model will be employed to an existent case of an Algerian East-West highway tunnel section, while using the code of calculation Plaxis3D tunnel. A detailed parametric survey that will be made to put in evidence influences it of the different parameters geometric and mechanical on the interaction between shallow tunnel and an existing piles and security objectives. And for understand furthermore the problem of interaction mechanism between micropiles and tunnel, principally when piles are positioned in close proximity to tunnels. The obtained findings show that the tunneling may affect in nearby piles a considerable bending moments, lateral deflection, compressive forces, and axial forces.